Preferential assimilation of NH4+ over NO3- in tea plant associated with genes involved in nitrogen transportation, utilization and catechins biosynthesis - Tang, Dandan (Plant science : an international journal of experimental plant biology, 2020)
Copyright © 2019 Elsevier B.V. All rights reserved.